2009
DOI: 10.1007/s00432-009-0646-9
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant DNA methylation of integrin α4: a potential novel role for metastasis of cholangiocarcinoma

Abstract: Taken together, these results suggest that loss of the integrin alpha4 gene is caused by aberrant DNA methylation of the 5'-CpG island site of the gene, and methylation of the integrin alpha4 gene can be a useful marker of metastasis of CC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…A similar complex regulation of gene expression was shown for another member of the same integrin subfamily integrin alpha4beta1-aberrant DNA methylation of its promoter region results in integrin alpha4 silencing in 55% of cholangiocarcinomas, 38 84.7% of 46 primary gastric tumors and 8 of 9 gastric cancer cell lines 39 while TSA treatment upregulated integrin alpha4 expression in hepatocellular carcinoma cell line Hep3B. 40 The obtained data show complexity of ITGA9 regulation in breast cancer cells that result in existence of ITGA9-expressing or ITGA9-non-expressing breast tumors.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 90%
“…A similar complex regulation of gene expression was shown for another member of the same integrin subfamily integrin alpha4beta1-aberrant DNA methylation of its promoter region results in integrin alpha4 silencing in 55% of cholangiocarcinomas, 38 84.7% of 46 primary gastric tumors and 8 of 9 gastric cancer cell lines 39 while TSA treatment upregulated integrin alpha4 expression in hepatocellular carcinoma cell line Hep3B. 40 The obtained data show complexity of ITGA9 regulation in breast cancer cells that result in existence of ITGA9-expressing or ITGA9-non-expressing breast tumors.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 90%
“…DNA hypermethylation leads to the downregulation and silencing of tumor suppressor genes during the pathogenesis of various human cancers [10,34-36]. Recently, genome-wide array-based studies have reported altered DNA methylation gene profiles in CRC [22-24].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, α (2)-integrin has been described to play a crucial role in hepatocarcinoma cell invasion and metastasis [30], while a transcriptional repression of the integrin α 4 gene caused by aberrant DNA methylation has been demonstrated in gastric cancer and cholangiocarcinoma [31]. …”
Section: Resultsmentioning
confidence: 99%